PENGABDIAN MASYARAKAT MELALUI PENGEMBANGAN EDUKASI EKOWISATA DENGAN PELIBATAN MASYARAKAT DI DANAU TEMPE KECAMATAN TEMPE KABUPATEN WAJO - Nurwana, Andi; Jamaluddin, Andi; Yuniarti, Andi (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2024)
Lake Tempe Is Fisherman. The problem that often arises related to the livelihood of the population is the availability of employment opportunities which are inadequate with population development as stated in the regional development planning of Wajo Regency. Especially for fishermen who live around Lake Tempe, if they only rely on income to fish in the lake, their income will be very limited, so to obtain additional income, ecotourism can be developed around the lake. This community service activity aims to increase public awareness about the potential. natural resources that can be used as a source of income, thereby increasing household income. This activity was carried out on August 31 2023, at Laelo Village, Tempe District. By obtaining results (1) the community can develop ecotourism in Lake Tempe, with full involvement by the community (2) community participation is quite good, so that this activity runs smoothly (3) increase community knowledge, especially fishermen, regarding ecotourism development to increase community income.